2015
DOI: 10.3389/fphys.2015.00209
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNAs in stress-responsive hepatic stellate cells during liver fibrosis

Abstract: The progression of liver fibrosis and cirrhosis is associated with the persistence of an injury causing agent, leading to changes in the extracellular environment and a disruption of the cellular homeostasis of liver resident cells. Recruitment of inflammatory cells, apoptosis of hepatocytes, and changes in liver microvasculature are some examples of changing cellular environment that lead to the induction of stress responses in nearby cells. During liver fibrosis, the major stresses include hypoxia, oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 130 publications
(132 reference statements)
0
33
0
1
Order By: Relevance
“…Previous studies have shown that hepatocytes and HSCs are the main intrinsic cell sources which contribute to the development of liver fibrosis458. To further clarify the biological roles of miR-706 in hepatic fibrosis, we performed in situ hybridization (ISH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that hepatocytes and HSCs are the main intrinsic cell sources which contribute to the development of liver fibrosis458. To further clarify the biological roles of miR-706 in hepatic fibrosis, we performed in situ hybridization (ISH).…”
Section: Resultsmentioning
confidence: 99%
“…Activated fibroblasts are characterized by their contractile capacity, the deposition of ECM and subsequently the production of hepatic fibrosis38. HSCs are regarded as the main source of fibroblasts4. Moreover, profibrogenic fibroblasts can also originate from portal fibroblasts, bone marrow stem cells and hepatocytes undergoing EMT678.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gének kifejeződését szabá-lyozzák poszttranszkripcionálisan. A csillagsejtek aktivá-lódásában szerepet játszanak a miR-29, a miR-146 és a miR-16 mikro-RNS-ek [49]. HCV-fertőzésben a miR-122 részt vesz a vírus stabilitásában és propagációjában [50][51][52].…”
Section: Epigenetikai Szabályozásunclassified
“…When hepatic stellate cells (HSCs) are subjected to stress such as hypoxia, oxidative stress or endoplasmic reticulum stress, they modulate fibrosis progression by induction of their activation toward a myofibroblastic phenotype, or by undergoing apoptosis, and thus helping fibrosis resolution [103]. General inflammation pathways also lead to liver fibrosis.…”
Section: Vi) Expert Commentarymentioning
confidence: 99%